2022
DOI: 10.1186/s12864-022-08761-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of the NHE gene family in Coilia nasus and its response to salinity challenge and ammonia stress

Abstract: Background In aquatic environments, pH, salinity, and ammonia concentration are extremely important for aquatic animals. NHE is a two-way ion exchange carrier protein, which can transport Na+ into cells and exchange out H+, and also plays key roles in regulating intracellular pH, osmotic pressure, and ammonia concentration. Results In the present study, ten NHEs, the entire NHE gene family, were identified from Coilia nasus genome and systemically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…These genes were found to be distributed randomly on 10 and 9 superscaffolds, respectively, which is consistent with the findings reported by Zhang et al (2019). The gene sequences of NHE and NKA gene family members were compared with those of O. mykiss, L. japonicus and S. maximus to name them and analyze the conserved motifs and structural domain characteristics (Berthelot et al, 2014;Figueras et al, 2016;Gao et al, 2022). The results revealed that the motifs and domains of the NHE genes were concentrated in the Na + /H + exchanger domains, which the identification of the NKA also showed that they closely association with Cation transporter/ATPase and Hydrolase domains, and the motifs and domains of different members were arranged in different patterns.…”
Section: Discussionsupporting
confidence: 84%
“…These genes were found to be distributed randomly on 10 and 9 superscaffolds, respectively, which is consistent with the findings reported by Zhang et al (2019). The gene sequences of NHE and NKA gene family members were compared with those of O. mykiss, L. japonicus and S. maximus to name them and analyze the conserved motifs and structural domain characteristics (Berthelot et al, 2014;Figueras et al, 2016;Gao et al, 2022). The results revealed that the motifs and domains of the NHE genes were concentrated in the Na + /H + exchanger domains, which the identification of the NKA also showed that they closely association with Cation transporter/ATPase and Hydrolase domains, and the motifs and domains of different members were arranged in different patterns.…”
Section: Discussionsupporting
confidence: 84%